Hyperparathyroidism Two Years after Radioactive Iodine Therapy in an Adolescent Male - Danielle L. Gomez; Dorothy I. Shulman (Hindawi Limited, 2014)
Primary hyperparathyroidism is a very rare complication following radioactive iodine therapy. There is typically a latency period of more than a decade following radiation exposure and, therefore, it is observed almost exclusively in adults. Consequently, pediatricians are not aware of the association. We present a case of primary hyperparathyroidism due to a solitary parathyroid adenoma occurring in an adolescent male two years following radioactive iodine treatment for papillary thyroid carcinoma. Periodic screening of serum calcium following ablative doses of radioactive iodine for thyroid cancer may be justified even in adolescents.